PENDAMPINGAN PENGEMBANGAN KARAKTER SDM PENGURUS ORGANISASI MAHASISWA PIAUD STAIN BENGKALIS MELALUI PENDEKATAN COACHING - Selian, Nurhaida; Muzaimah, Muzaimah; Sari, Nelta (Kreasi: Jurnal Pengabdian Masyarakat, 2024)
This community service activity focuses on assisting the development of character and human resources (HR) among the student organization leaders of the Early Childhood Islamic Education Student Association (PIAUD) at STAIN Bengkalis through a coaching approach. Coaching was selected as it facilitates holistic personal and professional growth, which is essential for shaping future leaders. The program aimed to enhance leadership, communication, and teamwork skills among the student organization leaders. This PkM was created using the method. The results of this initiative show significant improvements in various aspects of character and performance, positively impacting the organization's effectiveness. This program offers a model for HR character development that can be implemented in other student organizations.